Effectiveness of acupuncture in the treatment of chronic sciatica from herniated disks: a systematic review and meta-analysis - Qu, Zhen; Ju, Jiang-yi; Qin, Han; Ding, Yun-xia; Peng, Li-hua (Frontiers in Medicine, 2026)
IntroductionChronic sciatica, frequently attributable to lumbar disc herniation, imposes substantial burdens on patients’ quality of life and healthcare systems. Conventional interventions, including pharmacotherapy and physical therapy, are widely employed yet constrained by limited efficacy, necessitating the exploration of complementary modalities such as acupuncture. This systematic review and meta-analysis synthesizes evidence from randomized controlled trials (RCTs) published over the past decade (2015.05 – 2025.05) to evaluate the efficacy of acupuncture in alleviating leg pain intensity and improving functional mobility outcomes among patients with chronic sciatica.MethodsWe searched four databases (PubMed, EMBASE, Cochrane Library, Web of Science) for RCTs on acupuncture versus control (sham acupuncture, standard care, or conventional acupuncture). Studies included adults with sciatica from herniated disks, assessed via VAS for pain and ODI for function. Data were pooled using random-effects models with subgroup analyses for heterogeneity. Bias risk was assessed with the Cochrane tool.ResultsEleven RCTs (n = 868 participants, predominantly from China) were included. The results demonstrated that acupuncture significantly reduced leg pain VAS scores compared with those of controls (SMD = –1.08, 95% CI: –1.41 to –0.75), with consistent efficacy across the sham acupuncture (SMD = –1.05), standard care (SMD = –1.02), and conventional acupuncture (SMD = –1.12) subgroups. Acupuncture also improved functional disability (ODI: SMD = –0.57, 95% CI: –0.84 to –0.31; 7 studies, n = 621). The results indicate both statistical significance and clinical relevance, supporting acupuncture as an effective intervention.DiscussionAcupuncture effectively alleviates pain and aids functional recovery in chronic sciatica, highlighting its role in multidisciplinary pain management. However, methodological limitations in the extant literature necessitate cautious interpretation, and future high-quality RCTs are warranted to strengthen evidence-based clinical implementation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251067853, identifier (CRD420251067853).